Pawiwahan: Dinamika dan Tantangan pada Era Modern di Desa Penglipuran Bali - Arina Eliana Fitria; Naufal Rizki Ahmad Hanafi; Nur Farikhatun Nisa; Maudelyne Nasywa Maulida; Khoirin Zakiyah (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2026)
Penglipuran Traditional Village in Bali is known for its distinctive and well-preserved pawiwahan (marriage) traditions. This research aims to analyze the dynamics and adaptation of the pawiwahan system of the Penglipuran indigenous community amidst modernization currents. Using qualitative methods with a case study approach, data were collected through in-depth unstructured interviews with six key informants selected through purposive sampling, participatory observation, and documentary studies. The research was conducted over two days on April 29-30, 2025, in Penglipuran Traditional Village, Bangli Regency, Bali. Data triangulation and inductive analysis were used to ensure validity of findings. The research results show that pawiwahan in Penglipuran consists of four main types: Memadik, Nyentana, Pada Gelahang, and Ngerorod/Marangkat. Analysis using AGIL functionalism theory shows that pawiwahan plays a role in community adaptation (A) to modernization, goal attainment (G) of preserving traditional values, social integration (I), and latency (L) of cultural values. The Penglipuran community demonstrates cultural resilience through adaptive strategies that balance preserving the essence of pawiwahan with modern demands, particularly through procedural simplification, technology utilization, and intergenerational dialogue.